Sonoclot Signature Analysis in Patients with Liver Disease and Its Correlation with Conventional Coagulation Studies - Saxena, Priyanka (Hindawi Publishing Corporation, 2013)
Introduction. Liver disease patients have complex hemostatic defects leading to a delicate, unstable balance between bleeding and thrombosis. Conventional tests such as PT and APTT are unable to depict these defects completely. Aims. This study aimed at analyzing the abnormal effects of liver disease on sonoclot signature by using sonoclot analyzer (which depicts the entire hemostatic pathway) and assessing the correlations between sonoclot variables and conventional coagulation tests. Material and Methods. Clinical and laboratory data from fifty inpatients of four subgroups of liver disease, including decompensated cirrhosis, chronic hepatitis, cirrhosis with HCC and acute-on-chronic liver failure were analyzed. All patients and controls were subjected to sonoclot analysis and correlated with routine coagulation parameters including platelet count, PT, APTT, fibrinogen, and D-dimer. Results. The sonoclot signatures demonstrated statistically significant abnormalities in patients with liver disease as compared to healthy controls. PT and APTT correlated positively with SONACT (P < 0.008 and <0.0015, resp.) while platelet count and fibrinogen levels depicted significant positive and negative correlations with clot rate and SONACT respectively. Conclusion. Sonoclot analysis may prove to be an efficient tool to assess coagulopathies in liver disease patients. Clot rate could emerge as a potential predictor of hypercoagulability in these patients.